Recycling biosolids as cement composites in raw, pyrolyzed and ashed forms: A waste utilisation approach to support circular economy. (June 2021) - Roychand, Rajeev; Patel, Savankumar; Halder, Pobitra; Kundu, Sazal; Hampton, James; Bergmann, David; Surapaneni, Aravind; Shah, Kalpit; Pramanik, Biplob Kumar
Abstract: Ongoing management of biosolids has emerged as a major economic challenge for wastewater treatment facilities around the world. To tackle this challenge, it becomes imperative for the researcher community to identify various applications for this waste material, simultaneously supporting the government's closed-loop circular economy initiative. This research investigates the use of biosolids in raw, pyrolyzed (biochar), and ashed (bioash) forms as cement replacement materials. Detailed material characterization was carried out on the raw cementitious material followed by that on the hydrated cement composites using X-ray fluorescence, X-ray diffraction, energy-dispersive X-ray spectroscopy, scanning electron microscopy, carbon, hydrogen, nitrogen, and sulfur (CHNS) analysis, Xray micro-computed tomography and compressive strength test to identify their mechanical and physicochemical properties. The results show that the addition of 10% biosolids in the blended cement composite increased its total porosity by more than 21 times and decreased its compressive strength by 80% at 28 days of curing, indicating its potential use as an air-entraining admixture for the low-density concrete. However, the addition of 10% biochar brought about a strength improvement of ~278% and a reduction in its total porosity by ~87% compared to that of the biosolids blended cement composites. Partial replacement of cement with 10% bioash (ash form) showed ~66% reduction in its total porosity and 11% reduction in the 28-day compressive-strength compared to that of the biochar blended cement composites. Overall, this study demonstrates that the different forms of biosolids (raw, biochar, and bioash) can potentially be used as cement replacement materials with varied benefits in the cement and concrete industry. The recommendation for the future work is to carry out long-term durability studies on these blended cement composites for the ready uptake of this waste material by the construction industry. Graphical abstract: Image 1 Highlights: A comparative study of biosolids, biochar and bioash as cement replacement materials. Biochar provides the best performance among all the three forms. Potential application of biosolids identified as concrete air entraining admixture. XRD, XRF, SEM-EDS, CHNS and X-ray μCT used for material characterisation.